2022
DOI: 10.4103/sjmms.sjmms_480_21
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of 4C ISARIC Mortality Score in Critically ill COVID-19 Patients from Saudi Arabia

Abstract: Background: ISARIC mortality score is a risk stratification tool that helps predict the in-hospital mortality of COVID-19 patients. However, this tool was developed and validated in a British population, and thus, the external validation of this tool in local populations is important. Objectives: External validation of the ISARIC mortality score in COVID-19 patients from a large Saudi Arabian intensive care unit (ICU). Methods: This is a retr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
2
3
1
Order By: Relevance
“…Recently, another validation study of the ISARIC 4C Mortality Score in a critically ill cohort of 1,493 ICU patients in Saudi Arabia was conducted. 12 In this cohort, a similar AUC to ours was reported (0.81), providing additional support for the use of the 4C Mortality Score in a critical care setting. 12 In contrast to our study, they reported an overall higher mortality (38% vs 24%) despite a younger median age of their population (51.1 yr for survivors and 56.8 yr for nonsurvivors vs 64 and 75 yr old) and lower 4C Mortality Scores (6.3 and 12.4 vs 11 and 14).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Recently, another validation study of the ISARIC 4C Mortality Score in a critically ill cohort of 1,493 ICU patients in Saudi Arabia was conducted. 12 In this cohort, a similar AUC to ours was reported (0.81), providing additional support for the use of the 4C Mortality Score in a critical care setting. 12 In contrast to our study, they reported an overall higher mortality (38% vs 24%) despite a younger median age of their population (51.1 yr for survivors and 56.8 yr for nonsurvivors vs 64 and 75 yr old) and lower 4C Mortality Scores (6.3 and 12.4 vs 11 and 14).…”
Section: Discussionsupporting
confidence: 85%
“… 12 In this cohort, a similar AUC to ours was reported (0.81), providing additional support for the use of the 4C Mortality Score in a critical care setting. 12 In contrast to our study, they reported an overall higher mortality (38% vs 24%) despite a younger median age of their population (51.1 yr for survivors and 56.8 yr for nonsurvivors vs 64 and 75 yr old) and lower 4C Mortality Scores (6.3 and 12.4 vs 11 and 14). 12 This may reflect differences in patient demographics or variations in health care systems or practices.…”
Section: Discussionsupporting
confidence: 85%
“…On the other side, the prognostic stratification ability of the 4C-score, validated in a large European population, has already been confirmed among patients evaluated in the Emergency Department [ 18 , 19 ] and among those admitted to the Intensive Care Unit [ 20 ] or in the general ward [ 21 ], in different geographic areas. In our study group, which is one of the largest among the previously mentioned papers, 4C score outperformed all the other tools.…”
Section: Discussionmentioning
confidence: 98%
“…Albaie et al reported that the ISARIC 4C mortality score is useful to assess the prognosis of patients with type 2 diabetes mellitus presenting with COVID-19 with an AUC of 0.875 using a cutoff value of >14 [ 33 ]. Another study from Saudi Arabia found that the ISARIC 4C Mortality Score is an excellent tool to predict mortality in critically ill COVID-19 patients with an AUC of 0.81; the sensitivity was 70.5% and the specificity 73.97% with a cutoff value of >9 [ 22 ]. In addition, Crocker-Buque et al support using the ISARIC 4C Mortality Score for triaging COVID-19 patients at the time of admission and as a dynamic tool that provides accurate mortality risk information at any time during the hospitalization of COVID-19 patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, few studies have been conducted using the CURB-65 tool, showing good performance in predicting in-hospital mortality [ 20 , 21 ]. In addition, Aletreby et al (2021) recently validated the performance of the ISARIC score in a Saudi Arabian intensive care unit [ 22 ]. However, studies still need to be conducted to compare ISARIC-4C to the CURB-65 tool in the Saudi patient population, which is considered a research gap.…”
Section: Introductionmentioning
confidence: 99%